Dysequilibrium in a 5-year-old child with intrameatal vascular loops bilaterally. (March 2017) - Wen, Ming-Hsun; Cheng, Po-Wen; Young, Yi-Ho
Abstract: A 5 year-old boy was rather healthy until one month ago when loss of balance and muscle tone was noted by the parents. A battery of tests comprising electroencephalography, audiometry, caloric test and ocular vestibular evoked myogenic potential (oVEMP) test were performed, yet all tests showed normal responses. Conversely, cervical VEMP (cVEMP) test showed delayed responses bilaterally. MR imaging demonstrated bilaterally intrameatal vascular loops extending into both internal auditory canals. After a 3-month medication, delayed cVEMPs were resolved and returned to normal cVEMPs bilaterally, accompanied by subsidence of dysequilibrium.